Communal Coping as a Strategy to Enhance Family Engagement in Dilated Cardiomyopathy. (10th May 2022) - Burke, Wylie; Hovick, Shelly R.; Jordan, Elizabeth; Ni, Hanyu; Kinnamon, Daniel D.; Hershberger, Ray E.
Abstract : Background: Assuring that relatives are informed about a genetic diagnosis and have appropriate medical follow-up can be challenging. We hypothesize that communal coping (CC)—an approach in which a group views a stressor (such as a new genetic diagnosis) as our problem, versus my or your problem, and takes joint action to address it—can help families to address this challenge. A better understanding of CC could also inform counseling interventions to promote CC and family follow-up. Methods: In the Dilated Cardiomyopathy (DCM) PM study (Precision Medicine), living first-degree relatives of DCM probands were invited to undergo clinical screening; 31% of these did so. This research program offers the opportunity to determine the frequency of CC in DCM families, assess whether CC attitudes and actions occurred more commonly among families in which family members participated, and conduct prospective follow-up to evaluate family coping and counseling needs over time. Results: The proposed studies will provide evidence about the frequency of CC attitudes and actions among DCM families, assess the association of CC with increased family follow-up, and identify counseling needs related to family follow-up. Conclusions: The DCM PM study offers an opportunity to test the hypothesis that CC contributes to increased family follow-up and generate evidence to inform counseling interventions to encourage such follow-up.